Evaluating future urbanisation patterns in the Netherlands - Eric Koomen; Jan Groen (European Regional Science Association (ERSA), 2004)
Although the Netherlands is one of the most densely populated countries, two thirds of the land area are still under agricultural use. Major socio-economic changes are however expected for the agricultural sector. The increasing globalisation of economic relations in agriculture and the possible reduction of European price support to farmers are examples of such developments that may affect agricultural land use. At the same time other land use functions put increasing pressure on rural land in order to accommodate housing, employment, recreation and water storage. The present study takes a closer look at the expected spatial developments and simulates possible future land use patterns by using an economics based land use model. Two opposing scenarios of anticipated land use change are used to illustrate the possible extremes of future land use configurations. These scenarios vary both in their quantitative and qualitative description of the projected changes. The simulation of low-density residential areas in green areas will illustrate this approach. The development of these new rural living areas is currently a sensitive topic in the public debate on urbanisation. The simulated urbanisation patterns are evaluated in terms of their impact on spatial policy related issues through the application of newly developed indicators. For decades the Dutch government has strived for compact forms of urbanisation in order to preserve the remaining stretches of open space. The applied metrics of land use change will therefor focus on the concentration of urbanisation and the fragmentation of open space. The findings of this study may be especially interesting now Dutch spatial policy seems to be on the brink of loosening its traditional grip on spatial planning.
Keywords: 330